Population Origin and Heritable Effects Mediate Road Salt Toxicity and Thermal Stress - Conner, Lauren M.; Goedert, Debora; Fitzpatrick, Sarah W.; Fearnley, Amber; Gallagher, Emma L.; Peterman, Jessica D.; Forgione, Mia E.; Kokosinska, Sophia; Hamilton, Malik; Masala, Lydia A.; Merola, Neil; Rico, Hennesy; et al. (2023)
Human impacts on wild populations are numerous and extensive, degrading habitats and causing population declines across taxa. Though these impacts are often studied individually, wild populations typically face suites of stressors acting concomitantly, compromising the fitness of individuals and populations in ways poorly understood and not easily predicted by the effects of any single stressor. Developing understanding of the effects of multiple stressors and their potential interactions remains a critical challenge in environmental biology. Here, we focus on assessing the impacts of two prominent stressors affecting many organisms across the planet – elevated salinity (an increasingly common pollutant in freshwater habitats) and elevated temperature. We examined a suite of physiological traits and components of fitness across populations of wood frogs originating from ponds that differ in their proximity to roads and thus their legacy of exposure to road salt pollution. When experimentally exposed to road salt, wood frogs showed reduced survival, especially those from ponds adjacent to roads, and delayed time to metamorphosis. Family level effects mediated these outcomes, but high salinity generally eroded family level variance. When combined, exposure to both temperature and salt resulted in very low survival, and this effect was strongest in roadside populations. Taken together, these results suggest that temperature is an important stressor capable of exacerbating impacts from a prominent contaminant confronting many freshwater organisms in salinized habitats. More broadly, it appears likely that toxicity might often be underestimated in the absence of multi-stressor approaches.
Keywords: Climate change; Maladaptation; SCSU-student; amphibians; dept.bio; local adaptation; pollution; road salt

Genomic comparison of the temperate coral Astrangia poculata with tropical corals yields insights into winter quiescence, innate immunity, and sexual reproduction - Stankiewicz, Kathryn H.; Guiglielmoni, Nadège; Kitchen, Sheila A.; Flot, Jean-François; Barott, Katie L.; Davies, Sarah W.; Finnerty, John R.; Grace, Sean P.; Kaufman, Leslie S.; Putnam, Hollie M.; Rotjan, Randi D.; Sharp, Koty H.; et al. (bioRxiv, 2023)
Facultatively symbiotic corals provide important experimental models to explore the establishment, maintenance, and breakdown of the mutualism between corals and members of the algal family Symbiodiniaceae. The temperate coral Astrangia poculata is one such model as it is not only facultatively symbiotic, but also occurs across a broad temperature and latitudinal gradient. Here, we report the de novo chromosome-scale assembly and annotation of the A. poculata genome. Though widespread segmental/tandem duplications of genomic regions were detected, we did not find strong evidence of a whole genome duplication (WGD) event. Comparison of the gene arrangement between A. poculata and the tropical coral Acropora millepora revealed 56.38% of the orthologous genes were conserved in syntenic blocks despite ∼415 million years of divergence. Gene families related to sperm hyperactivation and innate immunity, including lectins, were found to contain more genes in A. millepora relative to A. poculata. Sperm hyperactivation in A. millepora is expected given the extreme requirements of gamete competition during mass spawning events in tropical corals, while lectins are important in the establishment of coral-algal symbiosis. By contrast, gene families involved in sleep promotion, feeding suppression, and circadian sleep/wake cycle processes were expanded in A. poculata. These expanded gene families may play a role in A. poculata’s ability to enter a dormancy-like state (“winter quiescence”) to survive freezing temperatures at the northern edges of the species’ range.
Keywords: dept.bio

Models of classroom assessment for course-based research experiences - Hanauer, David I.; Zhang, Tong; Graham, Mark J.; Adams, Sandra D.; Ahumada-Santos, Yesmi Patricia; Alvey, Richard M.; Antunes, Mauricio S.; Ayuk, Mary A.; Elena Báez-Flores, María; Bancroft, Christa T.; Bates, Tonya C.; Bechman, Meghan J.; et al. (Frontiers in Education, 2023)
Course-based research pedagogy involves positioning students as contributors to authentic research projects as part of an engaging educational experience that promotes their learning and persistence in science. To develop a model for assessing and grading students engaged in this type of learning experience, the assessment aims and practices of a community of experienced course-based research instructors were collected and analyzed. This approach defines four aims of course-based research assessment—(1) Assessing Laboratory Work and Scientific Thinking; (2) Evaluating Mastery of Concepts, Quantitative Thinking and Skills; (3) Appraising Forms of Scientific Communication; and (4) Metacognition of Learning—along with a set of practices for each aim. These aims and practices of assessment were then integrated with previously developed models of course-based research instruction to reveal an assessment program in which instructors provide extensive feedback to support productive student engagement in research while grading those aspects of research that are necessary for the student to succeed. Assessment conducted in this way delicately balances the need to facilitate students’ ongoing research with the requirement of a final grade without undercutting the important aims of a CRE education.
Keywords: dept.bio; peer-reviewed

Gathered from the Vine: A Survey of Seven Grapevine Viruses Within New England Vineyards - Dumas, Madeleine; Borges, Darlan Ferreira; Priesing, Stephanie; Tippett, Ethan; Ambrosio, Márcia Michelle de Queiroz; Luís da Silva, Washington (Plant Disease, 2023)
Vineyards in the Southeastern New England American Viticultural Area were surveyed for the incidence of seven major viruses: grapevine leafroll-associated viruses (GLRaV-1, GLRaV-2, GLRaV-3, and GLRaV-4), grapevine fanleaf virus (GFLV), tomato ringspot virus (ToRSV), and tobacco ringspot virus (TRSV). Viruses were detected by DAS-ELISA and confirmed by RT-PCR and Sanger sequencing. Multiple viruses were present in 19 out of the 25 vineyards surveyed between 2018 and 2020. GLRaV-3 (27.59%) was the most prevalent virus followed by GLRaV-4 (14.90%), GLRaV-1 (13.52%), GLRaV-2 (11.03%), ToRSV (6.34%), GFLV (5.24%), and TRSV (2.62%). Furthermore, phylogenetic analyses of the viral partial genome sequences acquired in this study revealed that the grapevine viruses present in this area are diverse, indicating that they may have been introduced from different sources. Our findings stress the need for improving the sanitary status of planting materials to avoid the introduction and dissemination of viruses to vineyards in this important wine-producing region of New England.
Keywords: New England; dept.bio; grapevine fanleaf virus; grapevine leafroll-associated virus; grapevine viruses; peer-reviewed; survey; tobacco ringspot virus; tomato ringspot virus